Same sky, different nights : a memoir - Jasentuliyana, Nandasiri (2013)
Autobiographical reminiscences of Nandasiri Jasentuliyana, a Sri Lankan lawyer.
"The journey of a Sri Lankan barrister, President Emeritus, International Institute of Space Law and Policy (IISL) from the chair of Deputy Director-General, United Nations Office at Vienna and Director, United Nations Office for Outer Space Affairs."
Includes index.
Keywords: Lawyers -- Sri Lanka -- Biography